Accuracy and practical applicability of hand print dimensions in estimation of stature of an individual in North Karnataka region - Kumar, Santosh; Sheelavant, Santosh (Journal of Indian Academy of Forensic Medicine, 2019)
Stature estimation from hand prints may support height estimation of suspects made by eye-witnesses which narrows down the pool of  nd suspects. 2 year MBBS students (Male-50, Female-50) of S Nijalingappa Medical College, Bagalkot aged between 20–29 years were  included in the study by purposive sampling. Height was recorded using standard stadiometer in a Frankfurt plane. Recording of the  handprints were taken in document scanner, edited using Photoshop software and measurements were taken using digital callipers to  the nearest millimetre: Hand print length (HPL), Hand print breadth (HPB), Length of individual finger print; Thumb print length  (TPL), Index finger print length (IFPL), Middle finger print length (MFPL), Ring finger print length (RFPL) and Little finger print  length (LFPL) were measured. Over all in males the left hand print length measurements correlated most with stature and in females  the right index finger print length measurements correlated most to stature estimation. According to cross-validated discriminant  analysis the hand dimensions that predicted the sex of the individual more significantly and accurately were the left hand palm breadth  and length and the right hand index finger length. The study concludes that one can estimate stature of an individual with reasonable  accuracy using hand print dimensions.
Keywords: Hand print; Stature; Identification; Karnataka